Factor analysis of the biomechanical parameters of pole vault run-up and takeoff: exploring sports performance - Li, X.; Xia, Z.; Lui, F.; Guo, J.; Wu, X.; Lui, X (Sports Biomechanics, 2022)
This study aimed to explore a parameter system and build a linear prediction model to effectively and comprehensively evaluate pole vault performance. The Qualisys motion capture system (200 Hz) and three Kistler force platforms (2000 Hz) were used to collect the athletes` kinematics and ground reaction force data of run-up and takeoff. Finally, 26 biomechanical parameters of 30 successful vaults of eight athletes were analysed by factor analysis, and linear regres-sion analysis was conducted on the extracted factors. Three factors were extracted by factor analysis: F1, F2, and F3. The mean max-imum COM height of the 30 vaults was 4.974 m. The score of F2 and F1 increased by 1, and the maximum COM height increased by 0.131 m and 0.112 m, respectively. The F3 did not participate in the prediction of performance. For the training of coaches and athletes, athletes of a higher stature need to expend more effort to achieve a higher training level. Furthermore, improving the speed, mechan-ical energy, and horizontal propulsion GRF of run-up and takeoff, as well as optimising the force generation strategy of the three lower limb joints in the takeoff support phase, help to achieve a good pole vault performance.